Development of Islamic Education Learning Materials: Its Implications for Islamic Education - Nadia Khairani; Rumaisha Nur Hamid; Febri Yola; Maharani Putri (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2024)
The rapid development of Islamic religious education, both in curriculum and in learning, encourages educational institutions, educators, (teachers or lecturers) to be able to innovate in Islamic Education learning. Researchers found that during this time, PAI learning in the eyes of students as stagnant learning, no progress in development made learning monotonous and boring. The purpose of this research is to find a learning model whose innovation is in the development of Islamic religious education learning materials. As a learning model that leads in the field of PAI learning based on Neuroscience and Quipper School. The research data was sourced through literature collections related to descriptions of scientific journals and taking notes on references to research works. both manually and digitally which focuses on the topic of Islamic religious education. This research is a literature study using qualitative methods. The results of this study found that the Neuroscience and Quipper School-based PAI learning material development model was able to facilitate students (students and students) in learning Islamic Education.